Utilization of beech wood flours obtained after thinning and beech cupula in wood plastic composite (WPC) production - Mücahit Şahin; İbrahim Halil Başboğa (Turkish Journal of Forestry, 2023)
This study aims to determine the effects of the evaluation of beech woods obtained from thinning, which are in the firewood class, and also beech cupulas as a filler in the manufacturing of wood plastic composite (WPC) on the technological properties of the composites. For this purpose, polypropylene (PP) based WPC production was carried out with the usage of 2 different fillers rate (0 or 50%) and three different types of lignocellulosic fillers (50% beech, 25% beech + 25% cupula or 50% cupula). In addition, maleic anhydride grafted polypropylene (MAPP) in 2 different ratios (0% and 3%) was used as a compatibilizing agent and the effects of MAPP usage were investigated. The mechanical (tensile strength, elongation at break, flexural strength, modulus of elasticity and impact strength) and physical (density and hardness) properties of the produced WPCs were determined in accordance with the relevant standards. As a result, when the lignocellulosic fillers were compared within themselves, it was seen that the highest mechanical properties were obtained with the usage of beech wood flour. The mechanical strength properties were negatively affected by the addition of cupula flours into the composite materials, and the mechanical properties were negatively affected by the increase in the cupula rates. Generally, the usage of MAPP has improved the mechanical properties of the WPCs. In Composite groups produced by using only beech wood flour together with MAPP, the highest values were obtained in all mechanical properties except elongation at break, and significant increases were observed compared to the control group. As a result of the study, PP-based WPC productions, in which beech wood flours and cupula flours are used as fillers, have been successfully carried out. It is thought that better performance will be achieved when beech wood flours are used alone or their cupulas are used together with beech wood flours and less than 25%.